Implications of Membrane Binding by the Fe-S Cluster-Containing N-Terminal Domain in the Drosophila Mitochondrial Replicative DNA Helicase - So, Minyoung; Stiban, Johnny; Ciesielski, Grzegorz L.; Hovde, Stacy L.; Kaguni, Laurie S. (Frontiers in Genetics, 2021)
Recent evidence suggests that iron-sulfur clusters (ISCs) in DNA replicative proteins sense DNA-mediated charge transfer to modulate nuclear DNA replication. In the mitochondrial DNA replisome, only the replicative DNA helicase (mtDNA helicase) from Drosophila melanogaster (Dm) has been shown to contain an ISC in its N-terminal, primase-like domain (NTD). In this report, we confirm the presence of the ISC and demonstrate the importance of a metal cofactor in the structural stability of the Dm mtDNA helicase. Further, we show that the NTD also serves a role in membrane binding. We demonstrate that the NTD binds to asolectin liposomes, which mimic phospholipid membranes, through electrostatic interactions. Notably, membrane binding is more specific with increasing cardiolipin content, which is characteristically high in the mitochondrial inner membrane (MIM). We suggest that the N-terminal domain of the mtDNA helicase interacts with the MIM to recruit mtDNA and initiate mtDNA replication. Furthermore, Dm Ind1, the known ISC donor for respiratory complex I and a putative donor for Dm mtDNA helicase, was identified as a peripheral membrane protein that is likely to execute membrane-mediated ISC delivery to its target proteins.